Characterization of BoaCRTISO Reveals Its Role in Carotenoid Biosynthesis in Chinese Kale - Jiang, Min; Zhang, Fen; Yuan, Qiao; Lin, Peixing; Zheng, Hao; Liang, Sha; Jian, Yue; Miao, Huiying; Li, Huanxiu; Wang, Qiaomei; Sun, Bo (Frontiers in Plant Science, 2021)
Carotenoids are organic pigments that play an important role in both plant coloration and human health; and they are a critical subject in molecular breeding due to growing demand for natural molecules in both food and medicine. In this study, we focus upon characterizing BoaCRTISO, the carotenoid isomerase gene at before the branch of the carotenoid biosynthetic pathway, which is expressed in all organs and developmental stages of Chinese kale, and BoaCRTISO, which is located in the chloroplast. The expression of BoaCRTISO is induced by strong light, red and blue combined light, and gibberellic acid treatment, but it is suppressed by darkness and abscisic acid treatment. We obtained BoaCRTISO-silenced plants via virus-induced gene silencing technology, and the silence efficiencies ranged from 52%–77%. The expressions of most carotenoid and chlorophyll biosynthetic genes in BoaCRTISO-silenced plants were down-regulated, and the contents of total and individual carotenoids and chlorophyll were reduced, except for β-carotene. Meanwhile, BoaCRTISO-silenced plants exhibited a phenotypes of yellowing leaves and inhibited growth. This functional characterization of BoaCRTISO provides insight for the biosynthesis and regulation of carotenoid in Chinese kale, and lays a foundation for molecular breeding to improve the carotenoid content and enrich the color of Chinese kale to benefit human health, nutrition and aesthetic enjoyment.